An Extended Scenario and Adjustment Model for Developing Countries - Samiei, Hossein (IMF Working Papers; Working Paper ;, 1993)
This paper discusses three important extensions to the developing country scenario and adjustment model used in the World Economic Outlook exercises. First, the model is augmented to include fiscal and monetary sectors and now explicitly captures links among government policy, investment, output and inflation. Second, the external sector is modified to allow domestic demand factors to influence imports, as well as allowing flexibility in the financing of imports. Third, the model system is extended to the group of net-creditor countries, and for the oil exporters within this group, oil exports are modeled separately. The revised model is estimated for each of the 95 developing countries and parameter estimates for each of the main equations are presented. The paper also reports the results of four simulation exercises to illustrate how the new model system may be used to quantify the effects of changes in domestic policies and in the external environment.